Investment drivers of country economic development - V. V. Khomenko; E. A. Ruzhnikov (Омский научный вестник: Серия "Общество. История. Современность")
The article deals with the key problems and ways of attracting investment resources to the national economy for the formation of sustainable economic growth accelerating scientific and technological progress, the development of the digital economy and the implementation of major infrastructure projects. Seven key investment drivers of the country economic development have been formed, a modern model of innovation and investment development of the national economy has been described. The authors specify the definition of the investment driver, describe the model of behavior of the subject of economic activity in the business environment. The method allows to access the potential profitability of attracting investment resources by the subject of economic activity, depending on the key parameters